Quality assessment of different commercial and local milk available in the local markets of selected area of Bangladesh (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study aimed to assess the organoleptic, physico-chemical, and microbial quality as well as the presence of any adulterants in different commercial and local milk samples.Materials and Methods: Three brands of ultra-high temperature (UHT) milk, three brands of pasteurized milk, and three raw milk samples were procured and analyzed for different quality tests. Consumer preference about the milk samples were studied by evaluating the organoleptic properties by a testing panel of 15 panelists. Physico-chemical, adulteration, and microbial analysis of the milk samples were performed by following different standard methods.Results: Most of the organoleptic properties were varied significantly at p ≤ 0.05 for UHT and pasteurized milk samples, while raw milk samples were equally acceptable to the panelists in most cases. From physico-chemical analysis, it was found that raw milk contained the highest amount of moisture (90.68%), whereas UHT had the lowest (87.60%), and other components were ranged as 0.68%–0.78% ash, 3.20%–3.58% protein, 3.15%–3.56% fat, 4.35%–4.62% lactose, 0.14%–0.22% acidity, 6.17%–8.95% solid not fat, 9.32%–12.40% total solid, and 1.026%–1.034% specific gravity. All adulteration tests responded negatively for raw samples, whereas commercial milk samples showed positive response only on added sugar test. Total standard plate count and coliform count tests showed that there was no microorganism in a detectable range in commercial milk samples, though raw samples had a significant amount.Conclusion: Though there were some fluctuations in some parameters of the three milk categories, but this study concluded that the quality of UHT and pasteurized milk were excellent with respect to parameters studied.J. Adv. Vet. Anim. Res., 7(1): 26-33, March 2020